Misa Online: Solusi Sementara dan Bermasalah - Fransiskus Sule (Jurnal Ledalero, 2021)
The ecclesiastical leaders have made policies that encourage the faithful to worship at home as a part of the effort to stop the spread of the coronavirus. Online Mass became a principal solution to fulfill Sunday's obligations. This article aims to evaluate the online Mass practice from the believers' perspective. To study people's attitudes towards online Masses, interviews were conducted and results showed that people in general were dissatisfied with this practice. Underlying the dissatisfaction were assumptions, which need to be clarified, for example, that Mass as being identical to Holy Communion is considered the only way to fulfill the Sunday's obligations. In fact, there are a number of religious practices and doctrinal teachings that could serve as better alternatives to the Eucharistic celebration on Sundays. This paper concludes that online Mass is not the right solution to the problem of worship during the pandemic.Key words: Covid-19, kewajiban hari Minggu, misa daring, Komuni Kudus, communio